The Principal's Strategies in Forming Student Character of SMP Al-Azhar Medan - Candra Wijaya; Ali Imran Sinaga; Widia Harahap (Budapest International Research and Critics University, 2020)
This study aims to reveals the principal leadership strategies in forming student character in Al-Azhar Middle School Medan. The approach used in this study is a descriptive analysis approach. According to Sumadi Suryabrata, a descriptive approach is a form of approach that is carried out using a systematic and accurate scribal (exposure or description) regarding the facts and characteristics of the population. This approach is used to describe and analyze the leadership strategy of the Al-Azhar Medan Middle School leadership.The research location is a place where researchers conduct research so that researchers get information in accordance with the themes discussed. This research was conducted at Jalan Pintu Air IV No. 214 Kwala Bekala, District: Medan Johor, Medan City, and North Sumatera. The result shows that the principal's leadership strategy in forming the character of students are exemplar, discipline, advice and assign tasks to teachers.